Human Dynamics Research in Smart and Connected Communities (Human Dynamics in Smart Cities,, 2018)
This book addresses how accelerating advances in information and communication technology, mobile technology, and location-aware technology have fundamentally changed the ways how social, political, economic and transportation systems work in today's globally connected world. It delivers on many exciting research questions related to human dynamics at both disaggregate and aggregate levels that attract the attention of researchers from a wide range of disciplines. Human Dynamics Research involves theoretical perspectives, space-time analytics, modeling human dynamics, urban analytics, social media and big data, travel dynamics, privacy issues, development of smart cities, and problems and prospects of human dynamics research. This book includes contributions on theoretical, technical, or application aspects of human dynamics research from different disciplines. Appealing to researchers, scholars and students across a wide range of topics and disciplines including: urban studies, space-time, mobility and the internet, social media, big data, behavioral geography and spatiotemporal-network visualization, this book offers a glimpse at the cutting edge of research on human dynamics.